Pembelajaran Pendidikan Agama Kristen Melalui Pendekatan Student Center Learning di SMA Sinar Pancasila Betun - Agustinus Seran (Publisher STPKat, 2023)
The purpose of this study is to determine the learning process of X1 students in Christian religious education subjects with the Student Center Learning method in improving student learning outcomes in grade XI of SMA Sinar Pancasila Betun. The method used in this study is qualitative descriptive. The results of the research show that teachers of Christian religious education subjects have used the Student Center Learning method in learning activities, but it is still not effective because subject teachers still use conventional methods, where in teaching and learning activities teachers do not provide opportunities for students to discuss between students and students with teachers. Learning Christian religious education based on Student Center Learning that has not been effective affects student learning outcomes so that the learning outcomes of grade XI students in Christian religious education subjects have not been maximized such as students have not understood the learning material of Christian religious education and have not been able to analyze Christian education learning materials.